Coal Mine Workers Safety Helmet in Li-Fi Data Stored in Cloud - Vishnukumar, A.; A.Nirmal Kumar, Dr.; Velmurugan, J.; Pavithra, P.; Poornima, K.; Sabareessh, S. (International Journal of Engineering and Technology, 2018)
Coal miners are more likely affected by the various threats   like   gas explosion ,sudden health  changes  and  issues,  severe  changes of the temperature and the moisture level .In this  paper  we  presented  the  design  of   the smart safety helmet for the coal miner using LI-FI, this helmet will be equipped with the network  of  sensors  such  as  the  heartbeat sensor ,humidity sensor,  gas sensor and the temperature  sensor  and  the  data  from these sensors will be transmitted  using light fidelity  technology  ,the  alert  messages  are given to the mobile phones and also through the  mail to the authorized person using IOT. Many accidents which occur in the mining industries   are   due   to   the      slow   data transmission     or  due  to  the  loss  of  data which  has  to  be  transmitted,  these  issues can  be  solved  by   using   the   light fidelity technology  as  it  is  known for the fast data transmission .